Beginning AI Bot Frameworks Getting Started with Bot Development - Biswas, Manisha (Apress, 2018)
Want to build your first AI bot but don't know where to start? This book provides a comprehensive look at all the major bot frameworks available. You'll learn the basics for each framework in one place and get a clear picture for which one is best for your needs. Beginning AI Bot Frameworks starts with an overview of bot development and then looks at Google Wit.ai and APi.ai functions, IBM Watson, AWS bots with Lambda, FlockOS and TensorFlow. Additionally, it touches on Deep Learning and how bot frameworks can be extended to mixed reality with Hololens. By the end, you'll have mastered the different bot frameworks available and finally have the confidence to develop intelligent AI Chatbots of their own.